Smart Word as a Metalingual Description (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article, metalingual comment smart word accompanying certain lexemes is considered on the material of Ukrainian internet discourse. Its importance for discourse self-presentation of language personality is shown alongside with its functions: maintaining the desired mode of communication, creating the evaluative meaning, disproving the opponent’s position with rhetoric arguments.
Keywords: metalanguage; connotation; evaluation; verbal self-presentation; agon communication